Solid‐State Batteries: Lithium–Graphite Paste: An Interface Compatible Anode for Solid‐State Batteries (Adv. Mater. 10/2019). Issue 10 (5th March 2019) - Duan, Jian; Wu, Wangyan; Nolan, Adelaide M.; Wang, Tengrui; Wen, Jiayun; Hu, Chenchen; Mo, Yifei; Luo, Wei; Huang, Yunhui
Abstract : The lithium/ceramic interface is represented using a ceramic cake with a lithium cream top and tiny "chocolate" particles inside. In article1807243, Wei Luo, Yunhui Huang, and co‐workers develop a lithium–graphite composite anode for all‐solid‐state lithium batteries. This composite anode facilitates the Li/garnet contact, and enables batteries with small voltage hysteresis, large critical current density, and impressive cycle life.